METHOD OF APPLICATION OF INDUSTRY 4.0 IN AUTOMOTIVE ASSEMBLY LINES - Endler, Cristian Lucas; Andrade Júnior, Pedro Paulo de (Brazilian Journal of Production Engineering, 2019)
The present work has the objective of proposing a method for applying the concepts of industry 4.0 in automotive assembly lines. In methodological terms, a bibliometric analysis was conducted in order to build a bibliographic portfolio with a high impact factor on the subject. Then, the systemic analysis of such portfolio was carried out, extracting the main key technologies of industry 4.0 for the automotive sector, which are: internet of things, machine-learning systems, edge computing, digital twins, big data, cloud manufacturing and cyber-physical systems in manufacturing. As a research result, it was obtained a five step methodology for the application of industry 4.0 in automotive assembly companies. These steps are: search for industry 4.0 know-how, definition of goals and targets, training of employees, application of industry 4.0 key technologies and evaluation of results / feedback.